2012
DOI: 10.1142/s0219633612500277
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Antioxidant Property of Gallic Acid and Its Derivatives

Abstract: We analyze the antioxidant property of four phenolic compounds i.e., gallic acid, methyl gallate, ethyl gallate, and 4, 5-dihydroxy 3-methoxy benzoic acid through the determination of bond dissociation enthalpy (BDE), vertical ionization potential ( IP v) in gas phase as well as in six different solvent medium. The theoretical trends of these phenolic compounds, based on BDE and IP, is compared with the scavenging activity towards HOCl . In addition, we compute and analyze the values of the density-based react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…For these secondary metabolites in a number of studies, significant antioxidant activity has been demonstrated (PEKKARINEN et al, 1999;MERKL et al, 2010;KALITA et al, 2012). These facts indicate that the secondary metabolites from the group of phenolic compounds, constitute the main components that contribute to the antioxidant activity of E. cyparissias extracts.…”
Section: Results and Disscusionmentioning
confidence: 92%
“…For these secondary metabolites in a number of studies, significant antioxidant activity has been demonstrated (PEKKARINEN et al, 1999;MERKL et al, 2010;KALITA et al, 2012). These facts indicate that the secondary metabolites from the group of phenolic compounds, constitute the main components that contribute to the antioxidant activity of E. cyparissias extracts.…”
Section: Results and Disscusionmentioning
confidence: 92%
“…Gallic acid derivatives (GADs) are naturally occurring polyphenols that act as antioxidants by efficiently scavenging free radicals. 4 The antioxidant properties of these natural polyphenols are assumed to occur by hydrogen atom transfer and single-electron transfer mechanisms. 4 Loranthus micranthus Linn is a hemi parasitic plant growing on different host trees and shrubs but depends on their host plant for water and mineral nutrition, despite the fact that they produce their own carbohydrates through photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…4 The antioxidant properties of these natural polyphenols are assumed to occur by hydrogen atom transfer and single-electron transfer mechanisms. 4 Loranthus micranthus Linn is a hemi parasitic plant growing on different host trees and shrubs but depends on their host plant for water and mineral nutrition, despite the fact that they produce their own carbohydrates through photosynthesis. 5 The isolation of polyphenols from L. micranthus parasitic on Hevea brasilensis and Kola acuminate with antioxidative potentials has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Again, Javan et al investigated computationally the H-atom vs electron transfer mechanism for antioxidant activity of some bromophenols and compared their observation to those for which the antioxidant activity was previously evaluated [10]. Analysis of antioxidant activity of various gallic acid derivatives as well as the values of some density-based reactivity descriptors was carried out by Kar et al and they found that phenolic compounds are more stable in gas phase than in solvent medium [11]. The antioxidant radical scavenging capacity of pyranoanthocyanins was investigated by Russo et al [12].…”
Section: Introductionmentioning
confidence: 99%